Du District au « grand Bamako » (Mali) : réserves foncières en tension, gouvernance contestée - Monique Bertrand (Cybergeo)
The institutional crisis of March of 2012 in Mali has revealed a more global political crisis that the governance of the Malian capital illustrates after more than a decade of decentralization illustrates well. With two millions of inhabitants, Bamako expresses sharp tensions of appropriation and use on its last public spaces within the administrative limits of the city, but also outside the District on land owned by local communities or claimed by the authorities of new rural municipalities settled on the urban fringe. The scale of land pressure and speculation indeed changes from the 2000s. Based on a fieldwork and a selection of conflicts, more and more often carried in justice, the article analyzes the confrontation of private interests, customary rights and public stakeholders, in a context of an economic liberalization and an institutional weakness. It also shows the continuity of a clientelist management of the land resource, which is recomposed by the multiparty rule during the Third Republic of Mali. The corruption and embezzlements on small or wider areas dedicated to the urban demand, contribute to discredit politics at the time they should be dedicated, according to number of international agendas, to the promotion of new partnerships and inclusive participation. These fights and shows of force on land properties and security of tenures basically show that social inequalities progress quickly in the urban society and express themselves more and more openly through collective protests.